TASK-SPECIFIC IONIC LIQUIDS FOR SEPARATION OF BENZENE AND CYCLOHEXANE USING EXTRACTIVE DISTILLATION - GONFA, GIRMA (2014)
Cyclohexane is used in several industrial applications. It is produced by the hydrogenation of benzene in the presence of hydrogen and catalyst. Hence, removal of the remaining benzene from the reactor's effluent stream is a very important. However, separation of benzene and cyclohexane mixture has been proved one of the most difficult tasks in the petrochemical industry because of their close boiling points and formation of an azeotropic mixture. Special separation processes such as extractive distillation is the main technology presently available to separate benzene and cyclohexane. In extractive distillation, a third component, usually known as entrainer, is added to change the phase equilibrium of the components. Up to date, two kinds of entrainers, liquid solvents and mixture of solid salt and liquid solvents, have been reported. However, the application of solid salts in extractive distillation is limited because of their difficulties in industrial operation and limited dissolution. In extractive distillation with liquid solvent, the solvent to feed ratio is high, which leads to high energy consumption. In addition, purification of the products and separation and recycling of solvents incurs additional cost on the separation process.